'Wilderness' and the Multiple layers of Environmental Thought. (1st June 1997) - Haila, Yrjo
Abstract : 'Wilderness' has become a widely used term in environmentalist discussion as a symbol for caring about nature. I review first the historical background: the term was adopted by US environmentalists in the 19th century to describe a nostalgic striving to get into contact with pure, unspoiled nature outside of human influence, in a sanctuary of genuineness and originality; this ideal was strengthened by its adoption by American nationalists. The background, however, lies in European Romanticism. Adoration of supposedly untouched nature arose as a counterpart to the depiction of nature as a unified system obeying eternal laws, amenable to human, rational exploitation. This idea of 'wilderness' cannot, however, be given any accurate empirical meaning and it rests on an assumption that a boundary can be drawn between 'natural' and 'unnatural' human activity, but this is impossible; furthermore, all assumed 'wilderness' areas have actually been inhabited by aboriginal people for millenia. The idea of 'wilderness' thus brings forth one example of how nature has been constituted as the 'other' of the western society. In this constitution, 'nature' and 'natural culture' have always belonged together. As an alternative, I discuss the possibility of recognising an element of 'wildness' inside human everyday existence. Henry David Thoreau was a pioneer of this view. Wildness everywhere present is a totally different idea from a wilderness having a concrete reference somewhere 'outside of' human influence. Thus, the fact of ecological crisis actually means rediscovery of nature rather than 'end of nature' as suggested by the famous slogan of Bill McKibben. I finish by suggesting that Thoreau's ever-present 'wildness' might be used as a building block along the path toward a 'nature contract', that is, a changed relationship to nature such that the prevailing attitude of domination and exploitation would be substituted with respect and care. This requires that the radical contextuality of human existence be recognised, and uncontrollable, 'wild' elements in this position be respected.